(untitled) (Journal of Health, Population and Nutrition, 2009)
In high- and low-performing districts of Bangladesh, the study explored the demand-side of maternal healthcare by looking at differences in perceived knowledge and care-seeking behaviours of women in relation to postpartum haemorrhage or eclampsia. Haemorrhage and eclampsia are two major causes of maternal mortality in Bangladesh. The study was conducted during July 2006-December 2007. Both postpartum bleeding and eclampsia were recognized by women of different age-groups as severe and life-threatening obstetric complications. However, a gap existed between perception and actual care-seeking behaviours which could contribute to the high rate of maternal deaths associated with these conditions. There were differences in care-seeking practices among women in the two different areas of Bangladesh, which may reflect sociocultural differences, disparities in economic and educational opportunities, and a discrimination in the availability of care. Key words: Beliefs; Care-seeking behaviour; Maternal mortality; Postpartum haemorrhage; Eclampsia; Qualitative research; Bangladesh doi: 10.3329/jhpn.v27i2.3328 J Health Popul Nutr 2009 April;27(2):156-169